Correlation between Duration of Social Media Use and Sleep Pattern Disorders In Children Aged 10-12 Years at SD Negeri Kepatihan 05 Jember - Romadhoni, Roza Riska; Anggraeni, Zuhrotul Eka Yulis; Maharani, Trias; Rohmah, Nikmatur; Savage, Eileen (Adi Husada Nursing Journal, 2024)
Social media usage can both positively and negatively affect children's sleep patterns, with potential negative effects on the quality and quantity of sleep. However, until now, more evidence is needed about the phenomenon in a population of school-age children. This study aims to analyze the relationship between the duration of social media use and sleep pattern disturbances in children aged 10-12 years at SD Negeri Kepatihan 05 based on the theory of problematic smartphone use. The research design uses a correlational approach with a cross-sectional approach. The population of children aged 10-12 years at SD Negeri Kepatihan 05 Jember is 250 respondents. The number of samples was 104 using simple random sampling. Data collection on the duration of social media use used an observation sheet while sleep pattern disturbances used a questionnaire sheet. Data analysis used rho sperm with the condition α ≤ 0.05. The results showed that there was a relationship between the duration of social media use and disturbed sleep patterns in children aged 10-12 years. The correlation in this study shows an r-value of 0.230 which identifies the degree of weak relationship, p-value of 0.019. The duration of social media use has been found to have a positive relationship with disturbed sleep patterns. This study concluded that prolonged social media use can disrupt sleep patterns in children, emphasizing the need for parental monitoring in this context.